2010
DOI: 10.1016/s0034-7094(10)70001-5
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Efficacy of the Intra-Articular Administration of High Doses of Morphine in Patients Undergoing Total Knee Arthroplasty

Abstract: The treatment group had lower NS than the control group in M1 and M2, while significant differences were not observed in the other moments. The time until the first request of analgesics was significantly higher in the treatment group, and analgesic consumption in the first 24 hours was also lower in this group. The incidence of side effects did not differ between both groups. We concluded that the postoperative IA administration of 10 mg of morphine promoted a longer period without rescue analgesics and reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 30 publications
1
19
1
Order By: Relevance
“…Previous studies have reported convincing evidence for lower morphine consumption in patients who had received LIA during TKA. 1,2,[21][22][23]27,28,30,31,33 However, none of the previous studies assessed morphine demand. In the present study, the reduction of both morphine demand and consumption in the LIA group further support the conclusion that the use of LIA improved pain control after TKA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported convincing evidence for lower morphine consumption in patients who had received LIA during TKA. 1,2,[21][22][23]27,28,30,31,33 However, none of the previous studies assessed morphine demand. In the present study, the reduction of both morphine demand and consumption in the LIA group further support the conclusion that the use of LIA improved pain control after TKA.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a reduction of 40% in morphine usage was considered to be a clinically relevant difference. 27 Based on previous studies, the mean (standard deviation) of total morphine usage was 20.6 (6.8) mg. 2,28 Using the above alpha and power values, a sample size of 11 patients per group was needed to detect a 40% reduction in morphine usage.…”
Section: Sample Sizementioning
confidence: 99%
“…16 Third, several trials found the effectiveness of peripheral opioid injections for local analgesia, such as intra-articular morphine after knee surgery. 17,18 Local opioid analgesic actions are pronounced in inflamed tissues. This may be attributed to the increased number of exposed opioid receptors and/or increased coupling with G-proteins (the degradation of perineural barriers and passage of agonists results in exposure of opioid receptors).…”
Section: Enrollmentmentioning
confidence: 99%
“…1,2) Epidural analgesia is one of the effective methods for pain management after total knee arthroplasty.However, epidural analgesia can cause dural puncture and lead to complications such as post-dural puncture headache, low back pain, cord injury, epidural hematoma and neurologic symptoms. Although, epidural analgesia has been reported to have very low epidural abscess rates, 3) infection could be a serious and life-threatening problem if there is no early diagnosis and treatment.…”
mentioning
confidence: 99%
“…1,2) Epidural analgesia is one of the effective methods for pain management after total knee arthroplasty.…”
mentioning
confidence: 99%